Development and validation of an electrochemiluminescent ELISA for quantitation of oral insulin tregopil in diabetes mellitus serum. (July 2017) - Ramaswamy, Shilpa G; Nayak, Vivek G; Jha, Sumit Kumar; Hegde, Vishika; Waichale, Vinit S; Melarkode, Ramakrishnan; Chirmule, Narendra; Rao, Anita U; Sengupta, Nilanjan
Aim: Tregopil, a novel PEGylated human insulin is in clinical development for oral delivery in diabetes treatment. The aim of the study was to develop and validate a sensitive and specific ELISA method for quantitating Tregopil in diabetes subjects on basal Glargine, since most commercially available insulin kits either do not detect Tregopil or show significant reactivity to Glargine.Methods : An electrochemiluminescent ELISA was developed and validated for Tregopil quantitation in diabetes serum.Results: The method has a LLOQ of 0.25 ng/ml, shows minimum cross-reactivity to Glargine and was successfully tested using a subset of samples from Tregopil-dosed Type 1 diabetes mellitus patients.Conclusion: The ELISA method is sensitive and can be used to support accurate measurement of Tregopil with no cross-reactivity to Glargine and its metabolites in clinical studies.